Implementation of Hypercontent-Based Web Media in Indonesian Language Learning for Poetry Writing Material in Elementary Schools - Iswahyuni Listyowati; Sabariah Sabariah (Universitas Negeri Surabaya, 2026)
The integration of digital learning media has become increasingly important in improving students’ literacy and creative writing skills in elementary education. However, the use of innovative digital media such as hypercontent-based learning is still limited, while conventional methods continue to dominate classroom practices. This study aims to analyze the effect of hypercontent-based web media compared to conventional methods and the role of gender in influencing the poetry writing ability of sixth-grade students at SDN Bareng 5 Jombang. The research employed a quantitative approach using a 2 × 2 factorial experimental design, with learning media (hypercontent-based web media vs. conventional method) as the first factor and gender (male vs. female) as the second factor. The research subjects consisted of 64 sixth-grade students who were equally divided into experimental and control groups. Data were collected using a validated and reliable poetry writing test supported by observation sheets. Data analysis was conducted using SPSS version 27 through a two-way ANOVA test. The results showed that learning media had a significant effect on students’ poetry writing ability (F = 79.686; p < 0.001), with students using hypercontent media achieving higher scores than those using conventional methods. Gender also had a significant effect (F = 24.784; p < 0.001), with female students demonstrating better poetry writing ability than male students. Furthermore, a significant interaction between learning media and gender was found (F = 24.273; p < 0.001), indicating that the effectiveness of hypercontent media differed by gender, with female students showing greater improvement. These findings indicate that hypercontent-based web media is more effective in enhancing students’ poetry writing skills and highlight the importance of integrating interactive digital media and gender-responsive strategies in creative writing instruction.